Characterization of PM2.5-bound trace elements, source apportionment, and assessment of associated human health risks during summer and winter in Greater Noida, the National Capital Region of India - Kumar, Vishnu; Yadav, Mudit; Behera, Sailesh N. (Frontiers in Environmental Science, 2022)
To examine the trends of particulate matter with aerodynamic diameter ≤ 2.5 µm (PM2.5) and its elemental constituents during two distinct seasons at a site away from the city center of Delhi and the National Capital Region (Delhi-NCR) of India, this unique study aimed at the development of source-receptor-effect linkages. This research paper presents results of occurrence, long-range transport (LRT), source apportionment and human health impact assessment of twenty-four PM2.5-bound trace elements (Al, Ba, Bi, Ca, Cd, Co, Cr, Cu, Fe, Ga, K, Li, Mg, Mn, Na, Ni, Pb, S, Se, Si, Te, Tl, Zn and Zr). The concentration of PM2.5 during winter (296 ± 45 µg/m3) was significantly higher than in summer (114 ± 48 µg/m3) and exceeded 24 h Indian standard on most of the measurement days. The seasonal concentration ratios (winter/summer) of individual elements varied from 1.7 (Si) to 5.9 (Tl). The backward trajectory of air masses showed that transboundary transport of pollutants occurred in the downwind direction during winter, indicating that this remote site was affected by transported particulates and local activities. The principal component analysis-absolute principal component score (PCA-APCS) model confirmed five significant sources, vehicles (22.3%), soil/road dust (23.1%), coal combustion (20.9%), open burning (13.8%) and other industries (10.2%) responsible for particulate emission. The results from the multiple path particle dosimetry model (MPPD) showed higher deposition of particulates in the human respiratory system occurred during winter (44%) than in summer (40%). The elements with crustal sources of origin had a higher deposition fraction in the head region (0.27 for Si) compared to elements of anthropogenic sources (0.13 for Li). The excess lifetime carcinogenic risk (ELCR) under winter episodic events increased significantly at 128×10-6 compared to the summer non-episodic period at 41×10-6.